Analysis of The Influence of Interactional Teachers' Teaching Style on Students' Activeness in The Learning Process in Indonesia - Ajerin Karim; Haratua Tiur Maria S; Venny Karolina (IJESS International Journal of Education and Social Science, 2023)
The teacher's teaching style has an important role in influencing the level of students’ involvement in learning. The interactional teacher's teaching style is able to encourage students to develop critical, creative thinking and problem-solving abilities. This research aims to determine the influence of interactional teachers' teaching style on students' activeness in learning. The method used in this research is descriptive quantitative research. Descriptive quantitative research is a research method whose aim is to determine the influence between two variables (dependent and independent). This research uses a simple linear regression test to determine the magnitude of the influence of one independent variable (interactional teacher teaching style) on the dependent variable (students' activeness). Data collection instruments were interviews, observation of interactional teachers’ teaching style, and student activeness questionnaire. Based on data analysis using a simple linear regression test, the magnitude of the influence of the independent variable on the dependent variable is 95.5%. Meanwhile, the calculated F value is 277.328 with a significance value of 0.000 < 0.05, indicating that there is an influence of interactional teachers’ teaching style on students’ activeness in the learning process of the tenth grade of SMA Negeri 1 Anjongan.